Assessing The Reliability of Module For Adolescence Psychological Well-Being In Malaysia Using The Application Of Sidek Model - Shahrul, Mohd.; Nazihah, Dayang Nurina; Nurafiqah, Dayang; Ahmadi, Raudhah; Salim, Johari Md; Nadia, Saidatul (Scientica Education Journal, 2024)
In this study, a module of adolescence psychological well-being in Malaysia using the application of Sidek module development model was developed by the Counselling and Psychology Association of Malaysia (PEKAMARA) to optimize psychological well-being o teenagers aged 13-25 years. The assessment of the adolescence psychological well-being in Malaysia module was meticulously crafted following a systematic approach encompassing needs analysis, objective formulation, content development, strategy selection, module production, implementation, and evaluation. Rigorous psychometric measures adapted from the Sidek module were employed to assess the validity and reliability of the adolescence psychological well-being module. The findings reveal a good level of validity, with a coefficient of 0.80, indicating that the module has successfully targets and addresses the specific psychological challenges faced by teenagers in this age group. Furthermore, the overall reliability coefficient was impressively high, with an Alpha Cronbach value of 0.93, underscoring the module's consistency in measuring desired outcomes across different facets of psychological well-being. The Sidek module development model leverages evidence-based practices from cognitive-behavioural therapy, positive psychology, and mindfulness, offering tailored interventions to enhance stress management, emotional regulation, resilience, and overall life satisfaction among adolescents. By integrating these methodologies, the module of adolescence well-being in Malaysia provides comprehensive support to address the complex mental health needs of young individuals during their formative years. This study contributes to advancing the field of mental health interventions for adolescents by demonstrating the efficacy of a structured and systematic approach in promoting positive psychological outcomes. The results highlight the importance of integrating theoretical frameworks into practical modules that are not only effective but also adaptable to diverse cultural contexts and individual needs.